Preparation method of low-cost artificially synthesized pyrophyllite-based mica

By using lera tailings to prepare modified lera-based mica, the limitations of natural mica in terms of strength and crystallization rate are solved, and the preparation of high-performance mica is achieved, reducing cost and environmental impact.

CN119841325AActive Publication Date: 2025-04-18HENAN JINGDUODUO NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510068645.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

In the prior art, natural mica has limitations in strength and crystallization rate, and its acquisition and processing process poses a burden to the environment, resulting in safety and performance problems when applied in high-tech fields.

Method used

Modified lerasite-based mica was prepared by mixing with sulfuric acid solution in the autoclave, intercalation reaction of urea and aluminum nitrate, and synthesis of electromelted magnesium, potassium fluorosilicate and potassium carbonate.

Benefits of technology

It significantly improves the mechanical properties and crystallization rate of mica, reduces production costs, provides a comprehensive utilization solution for lera tailings, and reduces resource waste and environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245029070000102
    Figure BDA0005245029070000102
Patent Text Reader

Abstract

The invention relates to the technical field of mica, and particularly discloses a preparation method of low-cost artificially synthesized pyrophyllite-based mica. The preparation method of the pyrophyllite-based mica comprises the following steps: mixing pyrophyllite tailings and a sulfuric acid solution in an autoclave, sealing, stirring, cooling and filtering to obtain impurity-removed pyrophyllite; urea and aluminum nitrate are added into dimethyl sulfoxide, stirring is performed, impurity-removed pyrophyllite is added, sealing is performed, constant-temperature water bath stirring is performed, cooling, calcining and heat preservation are performed, and cooling is performed to obtain modified pyrophyllite; and mixing the modified pyrophyllite, fused magnesite, potassium fluosilicate and potassium carbonate, carrying out ball milling, calcining, carrying out heat preservation, cooling at a cooling rate of 2-4 DEG C / min, calcining, carrying out heat preservation, and grinding to obtain the pyrophyllite-based mica. The pyrophyllite-based mica prepared by the method is high in strength, low in cost and suitable for large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mica, and in particular to a method for preparing low-cost artificially synthesized pyrophyllite-based mica. Background Art

[0002] As a mineral material with unique properties, mica plays an indispensable role in many fields such as electronics, aerospace, construction, and chemical industry. Its good insulation, high temperature resistance, chemical stability, and mechanical properties endowed by its unique crystal structure make it a key raw material for the manufacture of many high-tech products and traditional industrial products. However, the acquisition and application of mica materials currently face many severe challenges.

[0003] Traditionally, natural mica is the main source of mica materials. However, natural mica has great limitations in terms of strength. During the long and complex geological formation process, the interaction of various geological factors, such as pressure differences in different strata, temperature fluctuations, and uneven distribution of mineral components, has led to a large number of defects in the crystal structure of natural mica, and a high impurity content. This makes the strength of natural mica uneven, and it is difficult to meet some application scenarios in modern industry that require extremely high material strength. Taking the aerospace field as an example, aircraft parts need to maintain structural integrity under extreme mechanical environments. The insufficient strength of natural mica makes it very easy to be damaged when subjected to large external forces, vibrations or complex stress conditions, which seriously threatens the safe operation of the aircraft. In the field of electronic precision manufacturing, the strength and stability of materials are also strictly required. The performance shortcomings of natural mica limit the miniaturization and high performance of electronic products, and cannot meet the requirements of precision instruments for high precision and high reliability of parts.

[0004] The crystallization rate of natural mica also shows great instability. The crystallization process of mica is extremely demanding on the geological environment. Slight differences in factors such as mineral concentration, temperature gradient, and pressure change rate in the strata will have a significant impact on the crystallization of mica. This leads to the extreme scarcity of natural mica veins with high quality and high crystallization rate. Among the mica raw materials actually mined, a large amount of mica with low crystallization rate is mixed in. The low crystallization rate not only means that the mica crystals are not fully developed and their physical properties are greatly reduced, but also in the subsequent processing process, more manpower, material resources and time costs are required for screening and purification, which greatly reduces the efficiency of resource utilization.

[0005] From the perspective of sustainable development, the environmental problems caused by over-reliance on natural mica mining are becoming increasingly prominent. Large-scale open-pit and underground mining activities have seriously damaged mountain vegetation and surface structure, leading to ecological problems such as soil erosion and land desertification. At the same time, the large amount of tailings and waste generated during the mining process, if not properly handled, will cause serious pollution to the soil, water sources, etc., and cause ecological imbalance. In addition, with the rapid development of global industry, the market demand for mica continues to rise, but natural mica resources are limited, and the increasingly scarce status quo has caused its price to continue to rise. This not only brings heavy cost pressure to the downstream mica industry, but also restricts the healthy development of related industries to a certain extent.

[0006] The existing method of synthesizing mica using quartz sand and alumina as raw materials, although it has alleviated the dependence on natural mica to a certain extent, still has many disadvantages. First, the procurement cost of quartz sand and alumina is high, and with the changes in market supply and demand, the price fluctuates greatly, which makes it difficult to effectively control the production cost of mica. Secondly, the production process of this synthesis method is complicated, involving multiple reaction steps and strict reaction condition control, and requires high-precision production equipment and professional technicians, which undoubtedly further increases the production cost and technical threshold. In addition, a large amount of waste and pollutants will be generated during the production process, causing secondary pollution to the environment, and it is also unable to solve long-standing environmental problems such as tailings treatment. In summary, the development of a mica preparation technology that can overcome the performance limitations of natural mica, reduce costs, and achieve sustainable development has become a key issue that needs to be urgently addressed in the industry. Summary of the invention

[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a waterproof coating.

[0008] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0009] S1, pyrophyllite tailings and sulfuric acid solution are mixed in an autoclave, sealed and stirred, cooled, and filtered to obtain impurity-removed pyrophyllite;

[0010] S2, adding urea and aluminum nitrate to dimethyl sulfoxide, stirring, adding impurity-removing pyrophyllite, sealing and stirring in a constant temperature water bath, cooling, calcining and keeping warm, cooling, and obtaining modified pyrophyllite;

[0011] S3. Modified pyrophyllite, fused magnesia, potassium fluorosilicate and potassium carbonate are mixed, ball-milled, calcined and kept warm, then cooled at a cooling rate of 2-4°C / min, calcined, kept warm and ground to obtain pyrophyllite-based mica.

[0012] Preferably, in step S1, the weight ratio of pyrophyllite tailings to sulfuric acid solution is 100-120:600-700.

[0013] Preferably, in step S1, the concentration of the sulfuric acid solution is 0.9-1 mol / L.

[0014] Preferably, in step S1, the mixture is sealed and then stirred at a temperature of 165-175° C., a stirring time of 3-4 h, a stirring speed of 300-400 rpm, and an autoclave pressure of 5-8 MPa.

[0015] Preferably, in step S2, the weight ratio of urea, aluminum nitrate, dimethyl sulfoxide and impurity-removing pyrophyllite is 25-35, 5-15, 190-210: 90-110.

[0016] Preferably, in step S2, urea and aluminum nitrate are added to dimethyl sulfoxide and stirred for 0.5-1 h at a stirring speed of 300-400 rpm.

[0017] Preferably, in step S2, pyrophyllite for impurity removal is added, the mixture is sealed and stirred in a constant temperature water bath, the water bath temperature is 80-90° C., the constant temperature water bath stirring time is 22-26 h, and the stirring speed is 100-200 rpm.

[0018] Preferably, in step S2, calcination and heat preservation are performed, the temperature is increased to 400-500° C. at a heating rate of 5-15° C. / min, and the temperature is preserved for 2-3 hours.

[0019] Preferably, in step S3, the weight ratio of modified pyrophyllite, fused magnesia, potassium fluorosilicate and potassium carbonate is 250-350:150-250:100-200:40-60.

[0020] Preferably, in step S3, the ball milling time is 2-3 hours and the rotation speed is 250-350 rpm.

[0021] Preferably, in step S3, after ball milling, the temperature is first increased to 1400-1500°C at a heating rate of 4-6°C / min and calcined, and kept warm for 2-3 hours, and then cooled to 1200-1300°C at a cooling rate of 2-4°C / min and calcined, and kept warm for 2-3 hours.

[0022] Preferably, in step S3, the grinding is performed to a size of 40-80 mesh.

[0023] Beneficial effects:

[0024] The present invention opens up a new low-cost and sustainable way to prepare mica by using pyrophyllite tailings as raw materials, replacing traditional quartz sand and alumina with pyrophyllite, which not only significantly reduces the production cost, but also provides a practical and feasible comprehensive utilization plan for the treatment of pyrophyllite tailings, reducing resource waste and environmental burden.

[0025] The present invention, by modifying pyrophyllite, props up the interlayer structure of pyrophyllite, greatly promotes the formation and growth of mica crystals, so that pyrophyllite is significantly improved in strength and hardness, thereby enhancing the mechanical properties of the final product pyrophyllite-based mica, so that it can withstand greater external forces and is not easily damaged in practical applications. The intercalation reaction of urea and aluminum nitrate effectively supplements the aluminum element in pyrophyllite, accurately regulates pyrophyllite to an ideal silicon-aluminum ratio, and ensures the high-quality synthesis of pyrophyllite-based mica. At the same time, the alumina generated in situ between the pyrophyllite layers reduces the crystallization activation energy of fluorphlogopite, accelerates the crystal growth rate, and helps to form mica products with higher crystallinity and better quality, broadening its application prospects in electronics, aerospace and other fields with stringent requirements on material properties. DETAILED DESCRIPTION

[0026] The present invention will be further explained below in conjunction with specific embodiments.

[0027] The pyrophyllite tailings used below were purchased from Shaoxing Shangyu Pyrophyllite Mining Co., Ltd. and contained impurities such as iron;

[0028] Example 1

[0029] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0030] S1, 100g of pyrophyllite tailings and 600g of 0.9mol / L sulfuric acid solution were mixed in an autoclave, sealed and stirred at 165°C for 3h, with a stirring speed of 300rpm and a pressure of 5MPa, cooled and filtered to obtain impurity-removed pyrophyllite;

[0031] S2, add 25g urea and 5g aluminum nitrate to 190g dimethyl sulfoxide, stir for 0.5h, stirring speed is 300rpm, add 90g impurity-removing pyrophyllite, seal and stir in 80℃ constant temperature water bath for 22h, stirring speed is 100rpm, cool, heat to 400℃ at a heating rate of 5℃ / min, calcine, keep warm for 2h, cool to obtain modified pyrophyllite;

[0032] S3. Mix 250g of modified pyrophyllite, 150g of fused magnesia, 100g of potassium fluorosilicate and 40g of potassium carbonate, ball mill for 2h at a speed of 250rpm, heat to 1400℃ at a heating rate of 4℃ / min and calcine, keep warm for 2h, then cool to 1200℃ at a cooling rate of 2℃ / min and calcine, keep warm for 2h, grind to obtain pyrophyllite-based mica.

[0033] Example 2

[0034] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0035] S1, 120g of pyrophyllite tailings and 700g of 1mol / L sulfuric acid solution were mixed in an autoclave, sealed and stirred at 175°C for 4h, with a stirring speed of 400rpm and a pressure of 8MPa, cooled and filtered to obtain impurity-removed pyrophyllite;

[0036] S2, 35g urea, 15g aluminum nitrate were added to 210g dimethyl sulfoxide, stirred for 1h, the stirring speed was 400rpm, 110g impurity-removing pyrophyllite was added, sealed and stirred in a 90°C constant temperature water bath for 26h, the stirring speed was 200rpm, cooled, heated to 500°C at a heating rate of 15°C / min, calcined, kept warm for 3h, cooled, and modified pyrophyllite was obtained;

[0037] S3. Mix 350g of modified pyrophyllite, 250g of fused magnesia, 200g of potassium fluorosilicate and 60g of potassium carbonate, ball mill for 3h at a speed of 350rpm, heat to 1500℃ at a heating rate of 6℃ / min and calcine, keep warm for 3h, then cool to 1300℃ at a cooling rate of 4℃ / min and calcine, keep warm for 3h, grind to obtain pyrophyllite-based mica.

[0038] Example 3

[0039] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0040] S1, 110g of pyrophyllite tailings and 650g of 0.95mol / L sulfuric acid solution were mixed in an autoclave, sealed and stirred at 170°C for 3.5h, with a stirring speed of 350rpm and a pressure of 6.5MPa, cooled and filtered to obtain impurity-removed pyrophyllite;

[0041] S2, add 30g urea and 10g aluminum nitrate to 200g dimethyl sulfoxide, stir for 0.7h, stirring speed is 350rpm, add 100g impurity-removing pyrophyllite, seal and stir in 85℃ constant temperature water bath for 24h, stirring speed is 150rpm, cool, heat to 450℃ at a heating rate of 10℃ / min, calcine, keep warm for 2.5h, cool to obtain modified pyrophyllite;

[0042] S3. Mix 300 g of modified pyrophyllite, 200 g of fused magnesia, 150 g of potassium fluorosilicate and 50 g of potassium carbonate, ball mill for 2.5 h at a speed of 300 rpm, heat to 1450 ° C at a heating rate of 5 ° C / min and calcine, keep warm for 2.5 h, then cool to 1250 ° C at a cooling rate of 3 ° C / min and calcine, keep warm for 2.5 h, grind to obtain pyrophyllite-based mica.

[0043] Comparative Example 1

[0044] The difference between Comparative Example 1 and Example 3 is that the pyrophyllite is not modified;

[0045] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0046] S1, 110g of pyrophyllite tailings and 650g of 0.95mol / L sulfuric acid solution were mixed in an autoclave, sealed and stirred at 170°C for 3.5h, with a stirring speed of 350rpm and a pressure of 6.5MPa, cooled and filtered to obtain impurity-removed pyrophyllite;

[0047] S2. Mix 300 g of impurity-removed pyrophyllite, 200 g of fused magnesia, 150 g of potassium fluorosilicate, and 50 g of potassium carbonate, ball mill for 2.5 h at a speed of 300 rpm, heat to 1450 ° C at a heating rate of 5 ° C / min and calcine, keep warm for 2.5 h, then cool to 1250 ° C at a cooling rate of 3 ° C / min and calcine, keep warm for 2.5 h, grind to obtain pyrophyllite-based mica.

[0048] Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 3 is that aluminum nitrate is directly added to the impurity-free pyrophyllite for calcination, rather than first preparing urea and aluminum nitrate into an intercalation solution, and then reacting with the impurity-free pyrophyllite and then calcining;

[0050] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0051] S1, 110g of pyrophyllite tailings and 650g of 0.95mol / L sulfuric acid solution were mixed in an autoclave, sealed and stirred at 170°C for 3.5h, with a stirring speed of 350rpm and a pressure of 6.5MPa, cooled and filtered to obtain impurity-removed pyrophyllite;

[0052] S2, add 10g aluminum nitrate to 200g dimethyl sulfoxide, stir for 0.7h, stirring speed is 350rpm, add 100g impurity-removing pyrophyllite, seal and stir in 85℃ constant temperature water bath for 24h, stirring speed is 150rpm, cool, heat to 450℃ at a heating rate of 10℃ / min, calcine, keep warm for 2.5h, cool to obtain modified pyrophyllite;

[0053] S3. Mix 300 g of modified pyrophyllite, 200 g of fused magnesia, 150 g of potassium fluorosilicate and 50 g of potassium carbonate, ball mill for 2.5 h at a speed of 300 rpm, heat to 1450 ° C at a heating rate of 5 ° C / min and calcine, keep warm for 2.5 h, then cool to 1250 ° C at a cooling rate of 3 ° C / min and calcine, keep warm for 2.5 h, grind to obtain pyrophyllite-based mica.

[0054] Comparative Example 3

[0055] The difference between Comparative Example 3 and Example 3 is that: Step S2 does not perform calcination, and directly performs the subsequent fluorophlogopite preparation step;

[0056] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0057] S1, 110g of pyrophyllite tailings and 650g of 0.95mol / L sulfuric acid solution were mixed in an autoclave, sealed and stirred at 170°C for 3.5h, with a stirring speed of 350rpm and a pressure of 6.5MPa, cooled and filtered to obtain impurity-removed pyrophyllite;

[0058] S2, add 30g urea and 10g aluminum nitrate to 200g dimethyl sulfoxide, stir for 0.7h, stirring speed is 350rpm, add 100g impurity-removing pyrophyllite, seal and stir in a constant temperature water bath at 85°C for 24h, stirring speed is 150rpm, cool, and obtain modified pyrophyllite;

[0059] S3. Mix 300 g of modified pyrophyllite, 200 g of fused magnesia, 150 g of potassium fluorosilicate and 50 g of potassium carbonate, ball mill for 2.5 h at a speed of 300 rpm, heat to 1450 ° C at a heating rate of 5 ° C / min and calcine, keep warm for 2.5 h, then cool to 1250 ° C at a cooling rate of 3 ° C / min and calcine, keep warm for 2.5 h, grind to obtain pyrophyllite-based mica.

[0060] Comparative Example 4

[0061] The difference between Comparative Example 4 and Example 3 is that: in step S3, the system is not cooled down, and the calcination temperature is maintained at 1450° C. throughout the whole process;

[0062] A method for preparing low-cost artificially synthesized pyrophyllite-based mica comprises the following steps:

[0063] S1, 110g of pyrophyllite tailings and 650g of 0.95mol / L sulfuric acid solution were mixed in an autoclave, sealed and stirred at 170°C for 3.5h, with a stirring speed of 350rpm and a pressure of 6.5MPa, cooled and filtered to obtain impurity-removed pyrophyllite;

[0064] S2, add 30g urea and 10g aluminum nitrate to 200g dimethyl sulfoxide, stir for 0.7h, stirring speed is 350rpm, add 100g impurity-removing pyrophyllite, seal and stir in 85℃ constant temperature water bath for 24h, stirring speed is 150rpm, cool, heat to 450℃ at a heating rate of 10℃ / min, calcine, keep warm for 2.5h, cool to obtain modified pyrophyllite;

[0065] S3. Mix 300 g of modified pyrophyllite, 200 g of fused magnesia, 150 g of potassium fluorosilicate and 50 g of potassium carbonate, ball mill for 2.5 h at a speed of 300 rpm, heat to 1450 ° C at a heating rate of 5 ° C / min and calcine, keep warm for 5 h, and grind to obtain pyrophyllite-based mica.

[0066] Performance Testing

[0067] Mechanical strength: The compressive strength and flexural strength of the pyrophyllite-based mica prepared in Examples 1-3 and Comparative Examples 1-5 were tested according to JC / T 813-2024 standard. The results are shown in Table 1.

[0068] Crystallization rate: Keeping the raw material specifications and reaction conditions consistent, prepare pyrophyllite-based mica by the methods of Examples 1-3 and Comparative Examples 1-5, respectively, screen, and record the weight of mica as M1; then calculate the yield of mica under ideal reaction conditions as M2 based on the molar mass and stoichiometric relationship.

[0069] The calculation formula is:

[0070] Table 1 Performance test results

[0071]

[0072] Data Analysis:

[0073] It can be seen from the data of Examples 1-3 in Table 1 that the pyrophyllite-based mica prepared by the present invention has obvious advantages in mechanical strength and crystallization rate. On the one hand, the average compressive strength is about 1173.9 MPa, and the maximum can reach 1175.8 MPa. The average bending strength is about 169.7 MPa, and the maximum can reach 171.2 MPa, which shows that the mechanical strength of the mica is extremely superior and stable. On the other hand, the average crystallization rate is about 87%, and the maximum can reach 87.3%, which shows that the efficiency of preparing mica by this method is very high.

[0074] From the data of Example 3 and Comparative Example 1 in Table 1, it can be seen that intercalation modification plays an important role in improving the bending strength, compressive strength and crystallization efficiency of pyrophyllite-based mica. This is because the intercalation complex formed by urea and aluminum nitrate expands the interlayer structure of pyrophyllite after intercalation modification of pyrophyllite, providing a more favorable space for mica crystallization, making the crystals grow more fully, thereby improving the crystallization efficiency; at the same time, the modified structure enhances the internal bonding force of the mica, so that the bending strength and tensile strength are significantly improved.

[0075] From the data of Example 3 and Comparative Example 2 in Table 1, it can be seen that first preparing urea and aluminum nitrate into an intercalation solution and then reacting with the impurity-removed pyrophyllite is of key significance for improving the bending strength, compressive strength and crystallization efficiency of pyrophyllite-based mica. This is because the amino groups in the urea molecules coordinate with the aluminum ions of aluminum nitrate, which can make the aluminum ions evenly dispersed between the pyrophyllite layers, promote the uniform generation of aluminum oxide during subsequent calcination, provide more and more uniform crystal nuclei for mica crystallization, and greatly improve the crystallization efficiency; at the same time, this evenly distributed structure enhances the overall performance of mica and improves the bending strength and tensile strength.

[0076] From the data of Example 3 and Comparative Example 3 in Table 1, it can be seen that calcining at 450°C in step S2 is crucial to improving the bending strength, compressive strength and crystallization efficiency of pyrophyllite-based mica. This is because at this temperature, the gas generated by the decomposition of urea expands the interlayer structure of pyrophyllite, and aluminum nitrate decomposes to form aluminum oxide. The expanded interlayer structure provides sufficient space for mica crystallization, promotes crystal growth, and improves crystallization efficiency; and this structural optimization enhances the bonding effect inside the mica, thereby improving the bending strength and tensile strength.

[0077] From the data of Example 3 and Comparative Example 4 in Table 1, it can be seen that reasonable cooling in step S3 has a positive effect on improving the bending strength, compressive strength and crystallization efficiency of pyrophyllite-based mica. This is because during the cooling process, the atoms and molecules in the system have enough time to arrange in order, which helps to form a more complete and regular mica crystal structure, thereby improving the crystallization efficiency; at the same time, slow cooling can reduce the internal stress of the crystal, enhance the bonding force between crystals, and significantly improve the bending strength and tensile strength, while Comparative Example 4 is calcined at high temperature throughout the process, which is not conducive to the orderly growth and structural optimization of the crystal.

[0078] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing low-cost artificially synthesized pyrophyllite-based mica, characterized in that: The steps include: S1, pyrophyllite tailings and sulfuric acid solution are mixed in an autoclave, sealed and stirred, cooled, and filtered to obtain impurity-removed pyrophyllite; S2, adding urea and aluminum nitrate to dimethyl sulfoxide, stirring, adding impurity-removing pyrophyllite, sealing and stirring in a constant temperature water bath, cooling, calcining and keeping warm, cooling, and obtaining modified pyrophyllite; S3. Modified pyrophyllite, fused magnesia, potassium fluorosilicate and potassium carbonate are mixed, ball-milled, calcined and kept warm, then cooled at a cooling rate of 2-4°C / min, calcined, kept warm and ground to obtain pyrophyllite-based mica.

2. The method for preparing low-cost artificially synthesized pyrophyllite-based mica according to claim 1, characterized in that: In the step S1, the weight ratio of pyrophyllite tailings to sulfuric acid solution is 100-120:600-700.

3. The method for preparing low-cost artificially synthesized pyrophyllite-based mica according to claim 1, characterized in that: In step S1, the concentration of the sulfuric acid solution is 0.9-1 mol / L.

4. The method for preparing low-cost artificially synthesized pyrophyllite-based mica according to claim 1, characterized in that: In the step S1, the mixture is sealed and stirred at a temperature of 165-175° C., a stirring time of 3-4 h, a stirring speed of 300-400 rpm, and a pressure of the autoclave of 5-8 MPa.

5. The method for preparing low-cost artificially synthesized pyrophyllite-based mica according to claim 1, characterized in that: In step S2, the weight ratios of urea, aluminum nitrate, dimethyl sulfoxide and impurity-removing pyrophyllite are 25-35, 5-15, 190-210 and 90-110.

6. The method for preparing low-cost artificial synthetic pyrophyllite-based mica according to claim 1, characterized in that: In the step S2, calcination and heat preservation are performed, the temperature is increased to 400-500° C. at a heating rate of 5-15° C. / min, and the temperature is preserved for 2-3 hours.

7. The method for preparing low-cost artificially synthesized pyrophyllite-based mica according to claim 1, characterized in that: In step S3, the weight ratio of modified pyrophyllite, fused magnesia, potassium fluorosilicate and potassium carbonate is 250-350:150-250:100-200:40-60.

8. The method for preparing low-cost artificial synthetic pyrophyllite-based mica according to claim 1, characterized in that: In the step S3, the ball milling time is 2-3 hours and the rotation speed is 250-350 rpm.

9. The method for preparing low-cost artificially synthesized pyrophyllite-based mica according to claim 1, characterized in that: In the step S3, after ball milling, the temperature is first increased to 1400-1500° C. at a heating rate of 4-6° C. / min and calcined, and kept warm for 2-3 hours, and then cooled to 1200-1300° C. at a cooling rate of 2-4° C. / min and calcined, and kept warm for 2-3 hours.

10. The method for preparing low-cost artificial synthetic pyrophyllite-based mica according to claim 1, characterized in that: In the step S3, grinding is performed to a size of 40-80 mesh.

Citation Information

Patent Citations

  • Synthetic mica prepared from calcined talcum and preparation method and processing method of fluorophlogopite powder and fluorophlogopite pearlescent pigment

    CN101671034A

  • Process method for preparing ultra-fine high-brightness sericite powder by pyrophyllite

    CN101823723A

  • Artificial lens synthetic mica

    CN102674386A

  • Preparation method of high-temperature resistant tundish dry material based on pyrophyllite modification

    CN108840667A

  • Method for preparing glass fiber by compounding calcined bentonite and pyrophyllite

    CN112759269A

Cited By

  • In-situ mullite whisker toughened silicon-based ceramic core and preparation method thereof

    CN121104023A